Strategi Pemasaran Desa Wisata melalui Organizer MICE - Putu Gede Wiwin Gunawasika (IPM2KPE, 2021)
This study aimed to determine the role of the MICE organizer and the development strategy of the Bongkasa Pertiwi Tourism Village. This research is a qualitative descriptive study with data collection using questionnaires and interviews. The data obtained were analyzed in 3 stages, a) the input stage using the IFA and EFA matrices; b) analysis phase using SWOT matrix; c) the decision stage using the QSPM matrix. The results showed that at the input stage, the IFE matrix produced 16 internal factors and 12 external factors with an IFAS score of 3.53 and EFAS 3.6. The results of the SWOT matrix analysis showed that there are eight strategic factors of internal strength, and eight strategic factors of internal weakness. The results of the analysis using the QSPM matrix, there are eleven new strategies, and identified TAS values ​​and rankings. Conclusions, a) based on the SWOT Matrix and QSPM there are 11 alternative strategies in marketing Bongkasa Pertiwi Tourism Village; b) there are 3 roles of MICE, namely MICE as facilitator, MICE as promoter, and MICE as drafter. Keywords: Tourism Village, MICE Organizer, Marketing Strategy